Advantages of Large Meshes in Midwater Trawl - V., Vijayan; T., Joseph Mathai; H.N., Mhalathkar; M., Syed Abbas (Fishery Technology, 2025)
Results of investigations on the effect of incorporating larger meshes in a 10.3 m rectangular midwater trawl are presented in this paper. The midwater trawl with large meshes proved to be comparatively more efficient for the capature of lactarius sp., Trichiurus sp. and Arius sp. An increase in the catch of quality fish by 29.6% was also observed.